Republic of Slovenia : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2012)
The Slovenian banking system has been transformed by Slovenia's accession to the European Union. Banking sector regulation and supervision is generally in line with international standards. The global crisis affected Slovenia's economy significantly, and most banks in the system were also affected adversely. The authorities have attempted to reduce the effects of the financial crisis with several countercyclical fiscal policy measures and a program to provide liquidity to the financial sector. Strengthening the financial condition of the banking system is the key priority.